The Dwelling OF Two Previous Cases OF Kala Azar - Salman, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This is a contribution to study the dwelling of two previous cases of kala azar in the endemic area. In order to assess the possible ecological causes of the incidence and the prevalence of visceral leishmaniasis in central Iraq.